Event‐triggered distributed H∞$$ H_{∞ } $$ secure control for nonholonomic agents with dead‐zone inputs under attacks on sensors and actuators - Tan, Luy Nguyen (International journal of robust and nonlinear control, 2024)
Summary Distributed optimal control has been extensively investigated for nonholonomic mechanical agents (NMA). However, the existing methods have not yet taken into account vulnerabilities caused by malicious attacks on sensors and dead‐zone actuator links. The aim of this paper is therefore to propose a novel control scheme that not only achieves bounded L2$$ L_2 $$‐gain consensus performance and rejects dead‐zone disturbance but also mitigates the burden of communication resources and the effects of sensor and actuator attacks. Firstly, to estimate unmeasurable states and the unknown model of the attacks, event‐triggered (ET) observers are designed. Secondly, ET‐augmented control is proposed to transform Euler‐Lagrange dynamics into consensus tracking dynamics, from which the ET‐robust optimal control problem is formulated. Thirdly, the ET‐distributed H∞$$ H_{∞ } $$ secure control strategies are approximated synchronously via adaptive dynamic programming (ADP) and multi‐player differential game theory. Finally, a numerical example illustrates, on a networked multi‐robot system, the effectiveness of the proposed method.